In Situ Observation of Carbon Nanotube Layer Growth on Microbolometers with Substrates at Ambient Temperature - Svatoš, Vojtěch; Gablech, Imrich; Ilic, B Robert; Pekárek, Jan; Neužil, Pavel (Journal of applied physics, 2018)
Carbon nanotubes (CNTs) have near unity infrared (IR) absorption efficiency, making them extremely attractive in IR imaging devices. Since CNT growth occurs at elevated temperatures, integration of CNTs with IR imaging devices is challenging and has not yet been achieved. Here we show a strategy for implementing CNTs as IR absorbers using differential heating of thermally-isolated microbolometer membranes in a C2H2 environment. During the process, CNTs were catalytically grown on the surface of a locally-heated membrane while the substrate was maintained at an ambient temperature. CNT growth was monitored in situ in real time using optical microscopy. During growth, we measured the intensity of light emission and the reflected light from the heated microbolometer. Our measurements of bolometer performance show that the CNT layer on the surface of the microbolometer membrane increases the IR response by a factor of (2.3 ± 0.1) (mean ± one standard deviation of the least-squares fit parameters). This work opens the door to integrating near unity IR absorption, CNT-based, IR absorbers with hybrid complementary metal-oxide-semiconductor focal plane array architectures.